Pengaruh Financial Distress, Kepemilikan Institusional, dan Growth Opportunities terhadap Konservatisme Akuntansi - Yona Zulni; Salma Taqwa (Universitas Negeri Padang, 2023)
One of the principle in create a financial report is the accounting conservatism principle. Conservatism is said to more anticipating the loss than gain. This study aims to determine the influence of financial distress, institutional ownership, and growth opportunities on accounting conservatism in basic industrial and chemical manufacturing companies listed on the Indonesia stock exchange for the period 2017-2021. The sample was determined based on the purposive sampling method. The number of samples in this study is 169 samples with 5 observations periods. The data analysis used in this research is the test multiple linear regression analysis with SPSS version 25. The results showed that financial distress has a positive and significant effect on accounting conservatism, while institutional ownership and growth opportunities have no significant influence on accounting conservatism. This study contributes to add insight and knowledge in the field of accounting, about the factors that influence accounting conservatism in basic industrial and chemical manufacturing companies.